Trichoderma atroviride P1 Colonization of Tomato Plants Enhances Both Direct and Indirect Defense Barriers Against Insects - Coppola, Mariangela; Cascone, Pasquale; Lelio, Ilaria Di; Woo, Sheridan Lois; Lorito, Matteo; Rao, Rosa; Pennacchio, Francesco; Guerrieri, Emilio; Digilio, Maria Cristina (Frontiers in Physiology, 2019)
Numerous microbial root symbionts are known to induce different levels of enhanced plant protection against a variety of pathogens. However, more recent studies have demonstrated that beneficial microbes are able to induce plant systemic resistance that confers some degree of protection against insects. Here we report how treatments with the fungal biocontrol agent Trichoderma atroviride strain P1 to tomato plants induce responses that affect pest insects with different feeding habits: the noctuid moth Spodoptera littoralis (Boisduval) and the aphid Macrosiphum euphorbiae (Thomas). We observed that the tomato plant–Trichoderma P1 interaction had a negative impact on the development of moth larvae and on aphid longevity. These effects were attributed to a plant- response induced by Trichoderma, that was associated with transcriptional changes of a wide array of defence-related genes. While the impact on aphids could be related to the up-regulation of genes involved in the oxidative burst reaction, that occur early in the defence reaction, the negative performance of moth larvae was associated with the enhanced expression of genes encoding for protective enzymes (i.e. Proteinase Inhibitor I, Threonine deaminase, Leucine aminopeptidase A1, Arginase 2, Polyphenol oxidase), that are activated downstream in the defence cascade. In addition, the Trichoderma produced alterations in plant metabolic pathways lead to the production and release of volatile organic compounds that are involved in the attraction of the aphid parasitoid Aphidius ervi, thus reinforcing the indirect plant defence barriers. Our findings, along with the evidence available in the literature, indicate that the outcome of the tripartite interaction among plant, Trichoderma and pests is highly specific and only a comprehensive approach, integrating both insect phenotypic changes and plant transcriptomic alterations, can allow a reliable prediction of its potential for plant protection.